A Simplified Technique for Interventional Extracardiac Fontan. (January 2017) - Prabhu, Sudesh; Anderson, Ben; Ward, Cameron; Karl, Tom; Alphonso, Nelson
Purpose: We report a simple technique for an interventional extracardiac Fontan (ECF) procedure. Description: At the preparatory stage along with a bidirectional cavopulmonary connection (BCPC; cardiopulmonary bypass), a short piece of polytetrafluoroethylene (PTFE) tube graft is anastomosed to the inferior surface of the right pulmonary artery. Another longer PTFE graft is anastomosed to the transected inferior vena cava (IVC). A large medial opening in the lower PTFE graft is anastomosed to an atriotomy. These two PTFE tubes are anastomosed with a pericardial patch interposed between them. During the later interventional Fontan procedure, this pericardial patch is perforated using radiofrequency, and a covered stent is positioned entirely within the PTFE tubes, eliminating the window into the common atrium and leaving no intrapulmonary prosthetic material. Evaluation: The hemodynamics after the preparatory stage is similar to those following a BCPC, with uninterrupted flow from the IVC to the right atrium. On completion, there is a nonfenestrated Fontan circuit. Conclusion: Our technique of interventional Fontan, anatomically and hemodynamically, mimics a standard ECF procedure.